Repeatability of flicker modulation sensitivity measured using the Flicker-Plus test - Aiman Hafeez; Alison Binns; Sajni Bohra; Irene Ctori; John L. Barbur (PLoS ONE, 2025)
Purpose To evaluate the test-retest variability of the Flicker-Plus test for each of the two protocols measuring rod and cone-enhanced flicker modulation thresholds (FMT) in healthy individuals. A secondary aim was to evaluate the within-subject variability in repeated measurements. Methods Thirty healthy participants aged 19–71 years were examined. None had any history or signs of ocular disease. Monocular FMT were measured at the fovea (0°) and at an eccentricity of 5° in each quadrant, twice by the same investigator under identical conditions within a 2-week period under stimulus conditions that favoured either rods or cones to evaluate the between session repeatability. To assess the within-subject variability, binocular measurements for cone and rod-enhanced FMT were carried out on 15 different occasions over a period of 3-weeks in three of the participants. Coefficient of Repeatability (CoR) was calculated for inter-session repeatability and Bland Altman plots were created for graphical representation. Inter-class correlation coefficient (ICC) with 95% confidence intervals were estimated. Results Bland and Altman analysis shows that the mean bias is greater than zero in all 5 testing locations for both rod and cone-enhanced FMTs, suggesting that the threshold at the second visit tended to be lower than at the first, however the difference between visits was not statistically significant for any test condition (paired t-test, p < 0.05). In a sub analysis for those CoR was found to be higher in those aged <45years, compared to those aged ≥45 years. The correlation and agreement between the two measurements estimated by ICC analysis shows good (0.75–0.9) to excellent (>0.9) test-retest reliability of Flicker-Plus test for all measures. Conclusion The findings show good to excellent test-retest repeatability for the Flicker-Plus test. This was the case at all locations (foveal and peripheral), under both cone and rod-enhanced conditions. There was no evidence of significant learning effects.